Agricultural Mechanization Technology Tools in Paddy Field in Sekinchan, Selangor - Mohd Nawi, Nur Syazwani; Lam, Weng Yue (UUM Press, 2022)
Rapid development of technology has encouraged the use of agricultural mechanization technology in agriculture sector. The effective adoption of mechanization technology is important to improve management capacity and productivity among farmers. Thus, the purpose of this study is to investigate the usage of mechanization technology tool among farmers, explore the acceptance of mechanization technology and investigate influencing factors and risk of using mechanization technology tools among farmers in paddy industry. In this qualitative research, semi-structured interview was conduct with 3 farmers in Sekinchan. The finding of this study show the high usage of mechanization technology tools in paddy cultivation process. The finding also found that factor influence the use of mechanization technology which including factor from high cost of maintenance and modification, land consolidation system, advanced services, facility and infrastructure and human capital factor. The results show that an effective use of mechanization technology by farmers in Sekinchan. Government should actively give an effort to strengthen the functioning of mechanization technology to help achieving the goal of domestic rice supply.